The rapid rise of Russia's wheat exports: Price formation, spot-futures relations and volatility effects - Maximilian Heigermoser (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2023)
Over the past two decades, the Black Sea region has exhibited significantly growing wheat production and exports. In 2017/18, Russia ultimately became the world's largest wheat exporter, a position that was held by the USA for decades. Mostly serving destination markets in the Middle East and North Africa (MENA) region, Russian grain exports have become vital to ensuring regional and global food security. However, the Russian wheat export market shows several characteristics that can negatively affect agricultural trade, potentially jeopardizing food supply in import-dependent countries. First, in the face of severe harvest shortfalls, Russia and other Black Sea countries have frequently restricted grain exports in the past, which can contribute to price surges on international markets. Secondly, a functioning futures market reflecting Black Sea wheat does not yet exist. Grain traders therefore use established futures markets for price discovery and to hedge price risk in the Black Sea region, which can involve basis risk. Thirdly, previous research has suggested that Russian wheat exporters exercise market power in order to price discriminate among different destination markets. Further, grain exports can be hampered by deficiencies and bottlenecks in the Russian transportation and export infrastructure. Against this background, this dissertation analyzes how the ascent of Russian wheat exports changes the patterns of global physical trade, results in different pricing dynamics on physical and futures markets, and affects futures price volatility by changing trade policy. The methodological focus lies on time series econometrics, and price analysis in particular. Using vector autoregressive (VAR), autoregressive moving average (ARMA) and vector error correction models (VECM), the econometric analyses are conducted using price series recorded at varying frequencies (monthly to intradaily) to account for economic transactions occurring at different speed on physical compared to futures markets. An initial, descriptive analysis depicts the evolvement of Russian wheat exports over time, with respect to main destination regions. The focus on Russia's food trade with four key markets in the MENA region, namely Egypt, Turkey, Saudi Arabia and Iran, shows that grain trade is the central component in the respective trade ties. The deepening or loosening of food trade relations corresponds to the present state of respective political ties. Further, a market integration and price leadership analysis is conducted using a multivariate VECM approach. Analyzing the Egyptian wheat tender market as a proxy for the world wheat market, results suggest that European export prices play an increasingly important role for international wheat price formation, likely stemming from close regional proximity between European and Black Sea markets. These results are in line with the findings of a VAR analysis focusing on realized volatility relations between Black Sea spot and leading futures markets. Here, prices posted at the Euronext Paris (EPA) futures market are determined to affect the Black Sea physical market, while such an effect is not found concerning the Chicago Board of Trade (CBoT) market. Further, this analysis provides evidence of asymmetric adjustment to ruble jumps, which suggests that Russian wheat prices are more likely to increase in response to exchange rate movements than they are to decrease. The final ARMA analysis shows that news about Russian grain export restrictions significantly increase intraday seasonally adjusted realized volatility on the CBoT futures market. Further, elevated volatility can be determined in days preceding such news publications. These pre-announcement effects offer important insights into the validity of the Efficient Market Hypothesis (EMH) in the studied market. The restructuring of the world wheat market resulting from the rise of Russian wheat exports is ongoing. Particularly with respect to futures markets, leading exchanges still compete to establish a functioning Black Sea wheat futures contract that could potentially serve as novel global pricing benchmark. Moreover, the Russian government continues to intervene in the grain trade by imposing export taxes or quotas. Against the background of growing world populations and increased likelihood of harvest shortfalls due to climate change, it is stressed that unimpeded food trade is indispensable to ensure global food security. Policy recommendations aiming to prevent the introduction of food export restrictions are provided at the end of the dissertation. – – Über die letzten zwei Jahrzehnte stiegen Weizenproduktion und -exporte in der Schwarzmeerregion bedeutend an. Im Wirtschaftsjahr 2017/18 wurde Russland schließlich zum weltweit größten Weizenexporteur, nachdem die USA diese Position jahrzehntelang innegehabt hatten. Russische Getreideexporte bedienen speziell Märkte in der Region Mittlerer Osten und Nordafrika (MENA) und spielen für regionale und globale Ernährungssicherung eine zentrale Rolle. Allerdings kann der Agrarhandel durch zentrale Spezifika der russischen Weizenmärkte beeinträchtigt und so die Nahrungsmittelversorgung speziell in importabhängigen Staaten gefährdet werden. Erstens reagierte die russische Regierung in der Vergangenheit wiederholt mit Getreideexportbeschränkungen auf gravierende Ernteausfälle, was starke Preissteigerungen auf internationalen Märkten begünstigen kann. Zweitens existiert bisher kein funktionierender Warenterminmarkt, der speziell Schwarzmeerweizenmärkte repräsentiert. Getreidehändler nutzen deshalb etablierte Weizenterminmärkte zur Preisentdeckung und zur Absicherung von Preisrisiken in der Schwarzmeerregion, was jedoch mit Basisrisiko verbunden sein kann. Drittens hat vorangegangene Forschung gezeigt, dass russische Weizenexporteure Marktmacht zur Preisdiskriminierung zwischen verschiedenen Exportmärkten einsetzen können. Ferner können russische Getreideexporte durch unzureichende Transport- und Exportinfrastruktur behindert werden. Vor diesem Hintergrund analysiert diese Dissertation wie die expandierenden russischen Weizenexporte die Muster des physischen Getreidehandels verändern, zu neuen Preissetzungsdynamiken auf Kassa- und Terminmärkten führen und Preisvolatilität mittels Handelspolitikänderungen beeinflussen. Der methodische Fokus der Arbeit liegt auf Zeitreihenökonometrie und speziell auf Preisanalyse. Unter Verwendung von vector autoregressive (VAR), autoregressive moving average (ARMA) and vector error correction models (VECM) werden ökonometrische Analysen basierend auf Preisreihen unterschiedlicher Frequenz (monatlich bis intratäglich) durchgeführt. Auf diese Weise findet die unterschiedliche Geschwindigkeit ökonomischer Aktivität auf physischen und Terminmärkten Berücksichtigung. Zunächst fokussiert eine deskriptive Analyse auf die Entwicklung der russischen Weizenexporte in Hinblick auf verschiedene Exportmärkte. Bezogen auf vier zentrale Importländer der MENA-Region, nämlich Ägypten, Türkei, Saudi Arabien und Iran, machen russische Getreideexporte hier die zentrale Komponente der jeweiligen Handelsbeziehungen aus. Es können ferner Zusammenhänge zwischen der Vertiefung und Abschwächung der Handelsbeziehungen und Veränderungen in den jeweiligen politischen Beziehungen festgestellt werden. Mittels eines multivariaten VECM wird darauffolgend eine Marktintegrations- und Preisführeranalyse durchgeführt, die speziell auf den ägyptischen Weizentendermarkt als Proxy für den Weltweizenmarkt fokussiert. Die Ergebnisse zeigen, dass europäische Exportpreise eine zunehmend wichtige Rolle für die internationale Weizenpreisbildung spielen - wohl auch wegen geographischer Nähe zu den Märkten der Schwarzmeerregion. Diese Ergebnisse stimmen mit denen einer dritten Analyse zur Beziehung zwischen realisierter Volatilität an Kassa- und Terminmärkten überein. An der Euronext Paris (EPA) notierte Preisbewegungen übertragen sich demnach stärker auf die physischen Märkte der Schwarzmeerregion als jene an der Chicagoer Weizenterminbörse (CBoT). Fernere Indizien deuten auf asymmetrische Preisanpassungen nach Jumps im Rubelwechselkurs hin. Russische Weizenpreise steigen demnach in Folge von Wechselkursänderungen eher an, als zu fallen. Eine finale Analyse zeigt, dass Nachrichten zu russischen Getreideexportrestriktionen zu signifikanten Anstiegen der saisonal adjustierten intratäglichen Preisvolatilität an Terminmärkten führen. Erhöhte Volatilität lässt sich zudem an Tagen beobachten, die der Publikation dieser Nachrichten voran gehen. Gerade bezüglich der Validität der Effizienzmarkthypothese sind diese Ergebnisse für den betreffenden Terminmarkt aufschlussreich. Die Restrukturierung des Weltweizenmarktes, durch den Aufstieg russischer Weizenexporte bedingt, ist mitnichten abgeschlossen. Speziell in Bezug auf Weizenterminmärkte lässt sich konstatieren, dass führende Terminbörsen weiterhin um die Etablierung eines genuinen Schwarzmeerweizenkontraktes, der zur neuen globalen Preis-Benchmark avancieren könnte, konkurrieren. Darüber hinaus setzt auch die russische Regierung ihre Interventionen in den Getreidehandel mittels Exportsteuern und -quoten fort. Vor dem Hintergrund einer wachsenden Weltbevölkerung und steigendem Ernteausfallrisikos infolge des Klimawandels ist uneingeschränkter Nahrungsmittelhandel unerlässlich für die globale Ernährungssicherung. In dieser Hinsicht liefert diese Dissertation schließlich Politikempfehlungen, die darauf abzielen, Nahrungsmittelexportrestriktionen zukünftig zu verhindern.
urn:nbn:de:gbv:3:2-938914
Keywords: 330; Russia; wheat; exports; rapid; rise; price formation; spot-futures relations; volatility effects; Egypt; Turkey; Saudi-Arabia; Iran; Black Sea; multivariate cointegration; VECM; Vector Error Correction Model; Vector Autoregressive; VAR-X approach; Vector Autoregressive with Exogenous Variable; Generalized Autoregressive Conditional Heteroscedasticity; GARCH; Autoregressive moving average; ARMA-X approach